Examining the Intersectional Experiences of Ethnic Minority Women Within the Gendered Paradigm of Educational Institutions: A Case Study of Rajshahi University - Moniruzzaman; Hasan, Abu (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
This study aims to explore how ethnic minority women are facing discrimination at Rajshahi University. The research methodology involved the use of a qualitative case study design, which employed interviews to collect data from a sample of 17 undergraduate ethnic minority women at Rajshahi University. The study aimed to identify the influence of discriminatory outlook towards ethnic minority women in their academic experiences. There are significant biases against ethnic minority women in their academic experiences. The implications of this research highlight the need for increased attention to gender dynamics about ethnic minorities in society and the importance of creating more inclusive and equitable learning environments for all in society so that no one is facing discrimination based on their ethnic identity as well as gender status. This study contributes to the literature on gender and education by providing insight into the experiences of ethnic minority women and offering recommendations for authorities to promote a more equitable environment that eradicates the problems indicated in this research.